2012
DOI: 10.3390/cryst2030741
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of κ-(BEDT-TTF)2X Salts: Electron Correlations and Superconductivity

Abstract: Abstract:Heat capacity measurements of κ-(BEDT-TTF) 2 X (BEDT-TTF: Bis(ethylendithio) tetrathiafulvalene, X: counteranions) which are classified as two-dimensional (2D) dimer-Mott system are reported. At first, we explain structural and electronic features originated from rigid dimerization in donor arrangement in 2D layers. The antiferromagnetic Mott insulating phase located at low-pressure region in the phase diagram shows vanishing γ electronic heat capacity coefficient in the heat capacity, which claims op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…5 Recently, an unusual liquid-like state of spins was observed in organic charge-transfer salts with triangle lattice structures. Intensive investigations have been undertaken to unveil its origins and to produce further new magnetic states.…”
Section: 4mentioning
confidence: 99%
See 2 more Smart Citations
“…5 Recently, an unusual liquid-like state of spins was observed in organic charge-transfer salts with triangle lattice structures. Intensive investigations have been undertaken to unveil its origins and to produce further new magnetic states.…”
Section: 4mentioning
confidence: 99%
“…3,4 Moreover, thermodynamic measurements at low temperatures can clarify the nature of the ground states, since it is possible to extract spectroscopic information on the low-energy excitation spectrum from them. 5 Recently, an unusual liquid-like state of spins was observed in organic charge-transfer salts with triangle lattice structures. Intensive investigations have been undertaken to unveil its origins and to produce further new magnetic states.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…When the intra-dimer Coulomb repulsion U is larger than the width of the band constructed by the interdimer transfer integrals W, the system becomes a Mott insulating state with an antiferromagnetic ground state. On the contrary, if U < W, the system becomes a superconducting state [3]. No study has reported clearly on the synthesis of this material, although a good quality of this single crystal is required for precise magnetization measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Right now, β'-(BEDT-TTF)2ICl2 under 8.2 GPa has the highest critical temperature, Tc of 14.2 K for an organic superconductor [2]. The κ-(BEDT-TTF) 2Cu [N (CN) 2] Br (denoted as d8-κ-Br) consists of alternating layers of conducting donor, and it has a superconducting transition temperature, Tc of 11.5 K [3]. d8-κ-Br which eight hydrogens in an ethylene group of BEDT-TTF (bis (ethylene dithiol) tetrathiafulvalene) are substituted by deuteriums.…”
Section: Introductionmentioning
confidence: 99%